Psychometric evaluation and community norms of the GAD-7, based on a representative German sample - Kliem, Sören; Sachser, Cedric; Lohmann, Anna; Baier, Dirk; Brähler, Elmar; Fegert, Jörg M.; Gündel, Harald (Frontiers in Psychology, 2025)
IntroductionThe Generalized Anxiety Disorder-7 (GAD-7) scale is widely used to assess generalized anxiety symptoms in both clinical and general populations. However, updated psychometric evaluations and population norms for the German adult population are lacking. This study aims to examine the psychometric properties of the GAD-7 and provide representative population norms.MethodsA representative sample of the adult population in Germany (N = 2,519) was assessed. Item characteristics (means, standard deviations, inter-item correlations) were examined. Construct validity was evaluated through correlations with the PHQ-9 and BSI-18. Internal consistency was assessed using coefficient omega. Confirmatory factor analysis (CFA) was conducted to test the one-factor model, and measurement invariance across gender and age was examined using multi-group CFA.ResultsThe GAD-7 demonstrated strong internal consistency and construct validity. CFA supported the assumed one-factor model. Measurement invariance analyses indicated that the GAD-7 provides comparable measurements across gender and age groups. Updated population-based norms were established for the total sample and specific age groups.DiscussionFindings confirm the GAD-7 as a psychometrically sound measure for generalized anxiety in the general population. The updated norms enhance its applicability in clinical and epidemiological research, supporting its use for screening and assessment across diverse demographic groups.